Investigation of Indigenous Entomopathogenic Nematodes in Guangxi and Its Biological Control of Spodoptera frugiperda - Ailing Wang; Ming Fang; Jie Sun; Xianqin Wei; Weibin Ruan (Agronomy, 2022)
Spodoptera frugiperda has caused serious economic damage to various crops. Entomopathogenic nematodes (EPNs) can be used as biological control agents for many pests, including lepidopteran insects. In this study, 218 soil samples were collected from 46 sites in Guangxi, and EPNs were detected in 15 samples. The ITS region of the rDNA gene was used for the molecular identification of isolated nematodes. In total, four and eleven identified populations belonged to Heterorhabditis and Oscheius, respectively. A series of bioassays were conducted to examine the virulence of EPN isolates from Guangxi to control the larvae and pupae of S. frugiperda. The mortality of the third-instar larvae caused by EPNs was concentration dependent. The same dose of EPNs was used to control the third and sixth-instar larvae of S. frugiperda, and the virulence was lower in the sixth-instar larvae. S. frugiperda pupae were treated with different EPNs strains, and the adult eclosion rate of the treated group was significantly lower than that of the sterile water control group (93.3%). Therefore, EPNs could significantly inhibit the eclosion of S. frugiperda pupae. This study provides important information for the biological control of S. frugiperda with EPNs.